Management Functions In Overcoming Bullying In Basic Education Institutions: Fungsi Manajemen Dalam Mengatasi Bullying Pada Lembaga Pendidikan Dasar - Fajriyah, Aulia’ul; Fauji, Imam (Indonesian Journal of Innovation Studies, 2026)
General Background: Bullying remains a concern in basic education because it can disrupt students’ safety and comfort. Specific Background: SD Muhammadiyah 1 Candi addresses verbal and nonverbal bullying through public relations management and Islamic values. Knowledge Gap: The integration of public relations management, POAC functions, and Islamic values in school-based bullying management requires further contextual examination. Aims: This study analyzes management functions in preventing and handling bullying at SD Muhammadiyah 1 Candi. Results: Using a descriptive qualitative approach with interviews, observation, and documentation, the study found that planning, organizing, actuating, and controlling were implemented through anti-bullying policies, reporting and investigation procedures, monitoring, evaluation, and communication with parents and the community. Novelty: The study integrates POAC-based management and Islamic values through public relations in bullying management. Implications: The findings support the development of a safe, religious, and character-oriented school environment. Key Findings Highlights Verbal and nonverbal incidents were identified among students at the research site. School personnel coordinated reporting, investigation, monitoring, and evaluation with parents and the community. Islamic values were integrated with POAC functions to establish a safe, religious, and character-oriented environment. Keywords: Bullying, Public Relations, Management Functions, Islamic Values, Basic Education